Evaluation of silkworm pupae meal based calf starter diet on the performance of crossbred cattle calves - SAHIB, QAZI SHEHRIYAR; AHMED, HAIDER ALI; GANAI, ABDUL MAJEED; FAROOQ, JAVID; SHEIKH, GOWHER GULL; SHEIKH, ISLAM-UD-DIN; BEIGH, YASIR AFZAL (The Indian Journal of Animal Sciences, 2023)
The present experiment was conducted to evaluate the palatability, growth and economics of the silkworm pupae meal (SWPM) feeding, replacing fish meal (FM) in cattle calves. Crossbred cattle calves (15) around one-month of age were selected for the study and were divided into three equal groups (n=5) viz., T0 (100% FM), T1 (75% FM: 25% SWPM) and T2 (50% FM: 50% SWPM). To estimate the growth parameters fortnightly, a growth trial of 90 days was conducted, and a digestibility trial of 7 days was conducted at the end of experiment. The results revealed non-significant differences between the experimental groups in DMI, OMI, periodical body weight, body weight gain, average daily gain (ADG) (g/d), feed conversion ratio (FCR), feed conversion efficiency (FCE) (%), digestibility coefficients of dry matter (DM), organic matter (OM) and crude protein (CP). Significant differences were observed in digestibility coefficients of crude fibre (CF), ether extract (EE) and nitrogen free extract (NFE) between the groups. The digestible nutrients intake revealed significant difference only in CPI (g/d) with higher values in T0 followed by T1 and T2, but non-significant differences were observed in DDMI, DCPI and TDNI. The economics of feeding showed a decrease in the feed cost and feeding cost per kg body weight gain with increased inclusion of SWPM. Thus, it is concluded that costly FM can be replaced upto 50% level by SWPM without anyadverse effect on feed intake, growth and nutrient utilization of crossbred cattle calves.